Humanist Theology: Establish Ummah Toward A Tolerance - Muhammad Huzain (Al-Ulum, 2014)
The nature of religion has been endlessly discussed by philosophers, theologians, psychologists, and sociologists. They look at different aspects of religion as their interests and their purposes differ. Therefore, they formulate variety of definition of religion. Religion is seen to be difficult to define. But it is necessary to have a clear definition of religion as a starting point for religious studies. But in the globalization era, Muslim need theology basis which is strong. Theology term is to help enrich the muslim knowleadge of Islam. In the thought of Islam theology, means knowleadge which is content in relation beetwen God and the universe. Later, The draft formulation of this, are; How is the book theology in relation of book and religion pluralims? To focus to this formulation, it will be presented many questions, namely: First, How is the theology of consept in the book perspective? The Second, as a book guideline, how is theology implication toward the pluralism religion? Then this writing shows that theology (tauhid) is human awareness on thier believer toward the one god which cover it’s one of essence, action, atribute (characteristic). The unity of god essence is a furitification towards God. Yet, The fluralism is to be still unitied with strong bound, namely bound of essence of God.